A Normative Legal Study on PELAJAR Design in Gresik Regency - Suyanto Suyanto; Riski Dwi Prameswari; Devy Syanindita Roshida; Nafiatus Sintya Deviatin; Ika Ayudyanti; Anik Nur Kholifah; Tomi Indarto; Darin Farah Nabilah; Mohammad Setyo Puji Raharjo (Fakultas Syariah INSURI Ponorogo, 2026)
This Normative Legal Study on PELAJAR (Peta Kebutuhan Pelatihan Kerja) Design in Gresik Regency examines the misalignment between national vocational paradigms and local industrial exigencies. Using statute and conceptual approaches, the study scrutinizes Presidential Regulation No. 68/2022 alongside regional mandates to identify regulatory gaps. Crucially, the quantitative metrics presented, such as the 60–65% efficacy rate, are normative analytical constructs reflecting the